2017
DOI: 10.30544/264
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deformation on densification and corrosion behavior of Al-ZrB2 composite

Abstract: In the present investigation, aluminium based metal matrix composites (MMCs) were produced through powder metallurgical route. Different composites were processed by adding different amount of ZrB2 (0, 2, 4 and 6 wt. %) at three aspect ratios of 0.35, 0.5, and 0.65, respectively. The powder mixture was compacted and pressureless sintered at 550 °C for 1 h in controlled atmosphere (argon gas). The relative density of the sintered preforms was found to be 90%, approximately. Sintered preforms are used as workpie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The trend of hardness variation follows that of the relative density shown in Table 1 and Figure 3, in which Tn=200°C yields the highest HV value (292 HV), followed by Tn=195°C (270 HV), and the lowest hardness is 160 HV that is attained at Tn=205°C. It is obvious that high void/defect contents lead to low hardness due to their collapse within the solid material under loading [18] and vice versa, as is the case for other materials subjected to sintering/melting and solidification processes [28][29][30][31]. The results of hardness values of sintered parts for Tn=195°C (relative density: 81.9%, hardness: 270 HV) and 200°C (relative density: 97.6%, hardness: 292 HV) are higher than those obtained in other studies of 316L SS fabricated by FFF AM and conventional PM and MIM processes reported in literature, ~100 -175 HV [3,[6][7][8][9][10], which can be attributed to the high volume fraction of metal powder (metal loading) of 87.5 wt.% used in this study compared to 50 -80 wt.% used in those studies.…”
Section: Hardness Measurementsmentioning
confidence: 99%
“…The trend of hardness variation follows that of the relative density shown in Table 1 and Figure 3, in which Tn=200°C yields the highest HV value (292 HV), followed by Tn=195°C (270 HV), and the lowest hardness is 160 HV that is attained at Tn=205°C. It is obvious that high void/defect contents lead to low hardness due to their collapse within the solid material under loading [18] and vice versa, as is the case for other materials subjected to sintering/melting and solidification processes [28][29][30][31]. The results of hardness values of sintered parts for Tn=195°C (relative density: 81.9%, hardness: 270 HV) and 200°C (relative density: 97.6%, hardness: 292 HV) are higher than those obtained in other studies of 316L SS fabricated by FFF AM and conventional PM and MIM processes reported in literature, ~100 -175 HV [3,[6][7][8][9][10], which can be attributed to the high volume fraction of metal powder (metal loading) of 87.5 wt.% used in this study compared to 50 -80 wt.% used in those studies.…”
Section: Hardness Measurementsmentioning
confidence: 99%